2022
DOI: 10.3390/biom12060840
|View full text |Cite
|
Sign up to set email alerts
|

Role of Seipin in Human Diseases and Experimental Animal Models

Abstract: Seipin, a protein encoded by the Berardinelli-Seip congenital lipodystrophy type 2 (BSCL2) gene, is famous for its key role in the biogenesis of lipid droplets and type 2 congenital generalised lipodystrophy (CGL2). BSCL2 gene mutations result in genetic diseases including CGL2, progressive encephalopathy with or without lipodystrophy (also called Celia’s encephalopathy), and BSCL2-associated motor neuron diseases. Abnormal expression of seipin has also been found in hepatic steatosis, neurodegenerative diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 174 publications
0
8
0
Order By: Relevance
“…Seipin is known as the critical regulator of lipid metabolism. Loss of function mutation of Seipin led to not only lipid dysregulation but also neurological de cits, and the latter attracted augmenting attention [7,20]. In this study, we found abnormal lipid accumulation in SVZ of KO mice, accompanied by elevated glycerophospholipid and DG contents, resulting in abnormal SVZ neurogenesis, as well as olfactory memory dysfunction.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Seipin is known as the critical regulator of lipid metabolism. Loss of function mutation of Seipin led to not only lipid dysregulation but also neurological de cits, and the latter attracted augmenting attention [7,20]. In this study, we found abnormal lipid accumulation in SVZ of KO mice, accompanied by elevated glycerophospholipid and DG contents, resulting in abnormal SVZ neurogenesis, as well as olfactory memory dysfunction.…”
Section: Discussionmentioning
confidence: 53%
“…BSCL2, the Seipin coding gene, de ciency is responsible for type 2 congenital generalized lipodystrophy (CGL2), a rare autosomal disorder. CGL2 is characterized by the absence of whole-body adipose tissue and metabolic disorders such as hepatic steatosis, insulin resistance (IR) and dyslipidemia [20]. Noteworthy, individuals with CGL2 have an increased prevalence of mild mental retardation, which is not usually observed in CGL1 [10,38].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with Seipin gene mutation exhibit not only metabolic dyshomeostasis but also neurobehavioral impairments [ 12 ]. To assess the impacts of Seipin deficiency on rodent cognitive function and motor coordination, Seipin -/- mice were created and subjected to a series of behavioral tests.…”
Section: Resultsmentioning
confidence: 99%
“…Seipin loss-of-function mutations cause severe metabolic disturbances and neurological abnormalities in humans [ 12 ]. Seipin knockout mice also exhibit neurological deficits [ 19 , 42 ], emphasizing its crucial role in the nervous system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation